PENDEKATAN FENOMENOLOGIS DALAM STUDI PERBANDINGAN ETOS KERJA MANUSIA BUGIS-MAKASSAR DAN BANGSA JEPANG - Syamsuddin, M. Mukhtasar (Jurnal Filsafat "WISDOM", 2010)
AbstractThe result of phenomenological studies on comparative work ethos between Bugis-Makassar people and Japanese shows that both of them are able to positionize themselves appropriately in the dynamic world change which influences all aspects of social life.Cultural values of work ethos of Bugis-Makassar people and Japanese have similar sources which are values of traditional beliefs/ religions in Asia such as respect and worship to their ancestors. Nowadays the traditional religions still have a big impact in building their work ethos.Keywords: work ethos/ ethic, Bugis-Makassar, Japan.